Lake-level changes on the Tibetan Plateau and their relation to glacial melt - Cerny, Michaela (2017)
Lake-level changes are a popular target to study climate change responses on the Tibetan Plateau (TP). The large variety of research literature causes rather confusion than clarity: some researchers write that glacial melt is a significant contributor to lake-level increase (often without quantitative proof), while others claim that precipitation or permafrost degradation is a more significant contributor. Our first goal is to provide a comprehensive and quantitative review of this abundant literature. We collate the results from five independent studies that computed lake-level trends from the Ice, Cloud and Land Elevation Satellite (ICESat) mission during 2003-2009. We generate a database of these trends and examine the mutuality, hence the reliability of their results. Our second goal addresses the lack of quantified glacier meltwater contribution in the literature. For this objective, the output of a glacier evolution model on the TP is considered. We attribute glacial melt contributions to 133 endorheic lakes during 2003-2009 and compare these to past periods. Endorheic lakes and catchment basin attributes are obtained from the HydroBASINS and the newly published HydroLAKES databases. HydroLAKES provides new lake variables, such as estimations of lake depths and average shore slope (available for lakes <500 km2). As our last goal we investigate how lake area changes in the future 30 to 100 years could affect the Tibetan population. In the absence of better estimates, we assume that the current lake volume changes remain constant and that the lakes are circular. Then, we compare the geometry of conical and cylindric lake shore shapes. We show that a volume change in large lakes can be approached with cylindric shapes because shore slopes have a negligible impact. Our results demonstrate that the lake-level trends show no correlation to the meltwater contributions (r=0.04). Most large lakes (>500 km2) such as Nam Co are less affected by meltwater than small lakes. The lake area of most lakes changes on ...